PENGARUH AMBIGUITAS PERAN DAN KONFLIK PERAN TERHADAP PRESTASIKERJA MELALUI LOCUS OF CONTROL SEBAGAI VARIABEL MODERATOR PADAPT. LIMAS ANUGRAH STEEL SURABAYA - MUAH ASIH, ERNI (Jurnal Ilmu Manajemen (JIM), 2017)
This study aimed to analyze the effect ofrole ambiguity and role conflict on work performance through the locus of control as a moderator variable. The sample used in this study amounted to 50 employees are all employees ofPT. Limas Anugrah Steel analysis ofthe data used is Partial Least Square with the help ofsoftware SmartPLS3.0. The results of this study presented showed that role ambiguity and role conflict a significant positive effect on job performance. This is supported by indicators such as employment is accepted by the employer makes clear that work performance decreases. Locus of control is able Moderate effect between role ambiguity and role conflict on job performance. Moderation or moderator relationship can be shown by the phenomenon of the PT. Limas Anugrah Steel. Their willingness to believe in his own ability and believe in effort. The things that make employees eager to improve the work performance ofemployees. Keywords: Role ambiguity, Role conflict, Job performance, Locus of control<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px;" />